THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) AND ITS EFFECT ON THE CHARACTER OF JUNIOR HIGH SCHOOL STUDENTS IN SUNGAI PENUH CITY. - Ningsih, Pretty Elisa Ayu; Nurmalia Sari, Mike (Dharmas Education Journal (DE_Journal), 2024)
The Merdeka curriculum was introduced in 2020 as an effort to improve the quality of learning in schools. In the Merdeka Curriculum, students are not only formed into intelligent people but also have good character in accordance with the noble values of Pancasila. Although it has been introduced since 2020, in junior high schools in Sungai Penuh City itself, the implementation of P5 was only carried out in 2022, but until now not all schools have implemented it optimally and effectively. This study aims to assess the effectiveness of the implementation of the Pancasila Student Profile Strengthening Project (P5) in Junior High Schools in Sungai Penuh City and its effect on student character. This research uses a qualitative descriptive assessment method. Data were collected through interviews, observations, and document analysis in three schools namely SMP Negeri 1 Sungai Penuh, SMP Negeri 2 Sungai Penuh and SMP Negeri 9 Sungai Penuh. The results show that although teachers' understanding of P5 is still limited and there are still some obstacles faced by coordinators and facilitators in its implementation, the implementation of this project has had a positive impact on changes in student character, including increased cooperation, creativity, and self-confidence. This study recommends the need for training for teachers and parental support to optimize the implementation of P5.